Enhancing Students Vocabulary Mastery by Using Differentiated Instruction in SMAN 7 Soppeng - Nurmalayanti Amar; La Sunra La Sunra; Nur Aeni (Hasanuddin University, 2025)
Vocabulary mastery is a key challenge for EFL students in Indonesia, particularly at the senior high school level. This study aims to investigate the effectiveness of Differentiated Instruction (DI) in improving students' vocabulary mastery and engagement in English learning at SMAN 7 Soppeng. Employing a mixed-method explanatory sequential design, the research involved both quantitative and qualitative data collection. The quantitative phase used a quasi-experimental method with pre- and post-tests, while the qualitative phase employed semi-structured interviews to explore students' perceptions. This study was grounded in Tomlinson’s theory (2001) of Differentiated Instruction, which emphasizes tailoring instruction based on students’ readiness, interests, and learning profiles. In addition, Fredricks et al.’s (2004) theory of student engagement was used to examine behavioral, emotional, and cognitive aspects of learners’ involvement. The findings revealed that DI significantly enhanced students’ vocabulary acquisition and promoted higher levels of engagement. These results suggest that implementing DI is a beneficial instructional strategy to address diverse learning needs and foster active participation in vocabulary learning.